Cis-Repression of Foxq1 Expression Affects Foxf2-Mediated Gene Expression in Palate Development - Xu, Jingyue; Liu, Han; Lan, Yu; Jiang, Rulang (Frontiers in Cell and Developmental Biology, 2021)
Disruption of FOXF2, encoding a member of the Forkhead family transcription factors, has been associated with cleft palate in humans and mice. FOXF2 is located in a conserved gene cluster containing FOXQ1, FOXF2, and FOXC1. We found that expression of Foxq1 is dramatically upregulated in the embryonic palatal mesenchyme in Foxf2-/- mouse embryos. We show here that the Foxf2 promoter-deletion mutation caused dramatically increased expression of the cis-linked Foxq1 allele but had little effect on the Foxq1 allele in trans. We analyzed effects of the Foxf2 mutation on the expression of other neighboring genes and compared those effects with the chromatin domain structure and recently identified enhancer-promoter associations as well as H3K27ac ChIP-seq data. We show that the Foxf2 mutation resulted in significantly increased expression of the Foxq1 and Exoc2 genes located in the same topologically associated domain with Foxf2 but not the expression of the Foxc1 and Gmds genes located in the adjacent chromatin domain. We inactivated the Foxq1 gene in mice homozygous for a Foxf2 conditional allele using CRISPR genome editing and generated (Foxf2/Foxq1)+/- mice with loss-of-function mutations in Foxf2 and Foxq1 in cis. Whereas the (Foxf2/Foxq1)-/- mice exhibited cleft palate at birth similar as in the Foxf2-/- mice, systematic expression analyses of a large number of Foxf2-dependent genes revealed that the (Foxf2/Foxq1)-/- embryos exhibited distinct effects on the domain-specific expression of several important genes, including Foxf1, Shox2, and Spon1, in the developing palatal shelves compared with Foxf2-/- embryos. These results identify a novel cis-regulatory effect of the Foxf2 mutation and demonstrate that cis-regulation of Foxq1 contributed to alterations in palatal gene expression in Foxf2-/- embryos. These results have important implications for interpretation of results and mechanisms from studies of promoter- or gene-deletion alleles. In addition, the unique mouse lines generated in this study provide a valuable resource for understanding the cross-regulation and combinatorial functions of the Foxf2 and Foxq1 genes in development and disease.